COMPLEX SUPERVISION OF PHYSICAL AND TECHNICAL-TACTICAL PREPARATION OF DISABLED FOOTBALL PLAYERS - Ziyayev Abdurakhmon Abdullayevich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Work relevance. In our country to football very big attention is being directed. Our country different Term teams international in competitions participation to success achieved is coming Opportunity limited people physical development level increase for rehabilitation events right to the road should be put. The same at the time many physical rehabilitation styles there is and rehabilitation of the process structure pathology types dependence open given.